2010
DOI: 10.1371/journal.pone.0008924
|View full text |Cite
|
Sign up to set email alerts
|

Myc Is Required for Activation of the ATM-Dependent Checkpoints in Response to DNA Damage

Abstract: BackgroundThe MYC protein controls cellular functions such as differentiation, proliferation, and apoptosis. In response to genotoxic agents, cells overexpressing MYC undergo apoptosis. However, the MYC-regulated effectors acting upstream of the mitochondrial apoptotic pathway are still unknown.Principal FindingsIn this study, we demonstrate that expression of Myc is required to activate the Ataxia telangiectasia mutated (ATM)-dependent DNA damage checkpoint responses in rat cell lines exposed to ionizing radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 45 publications
3
52
2
2
Order By: Relevance
“…For example, c-myc is an established oncogene in various types of cancer 35,36 however, overexpression of c-myc surprisingly sensitizes cells to apoptosis. [37][38][39] E2F1 is another transcription factor that governs cell cycle progression and also regulates apoptosis under conditions of genotoxic stress. 40 PELP1 overexpressing human breast cancer cells undergo significantly more apoptosis when treated with 9-cis-RA.…”
Section: Resultsmentioning
confidence: 99%
“…For example, c-myc is an established oncogene in various types of cancer 35,36 however, overexpression of c-myc surprisingly sensitizes cells to apoptosis. [37][38][39] E2F1 is another transcription factor that governs cell cycle progression and also regulates apoptosis under conditions of genotoxic stress. 40 PELP1 overexpressing human breast cancer cells undergo significantly more apoptosis when treated with 9-cis-RA.…”
Section: Resultsmentioning
confidence: 99%
“…3). In addition, upon exposure to IR, c-Myc plays a crucial role in the activation of ATM checkpoints [63]. Another explanation is totally contrary to the first, namely, that the proliferative role of Wnt signaling is temporally inhibited in response to IR by three possible manners.…”
Section: Dna Damage Checkpoint Responsesmentioning
confidence: 97%
“…We have previously reported that AAV2 infection upregulated expression of both the dimer-and monomer forms of c-Myc in multiple breast cancer lines tested, 16 which suggested that AAV2-regulated expression and/or stabilization of c-Myc could serve to amplify proliferation signals which allow the breast cancer cells to bypass cell cycle checkpoint controls in the presence of damaged cellular DNA. 16 On the other hand, c-Myc is also a protein which limits growth by sensitizing cells to apoptosis, 43 and which has the added potential to regulate DNA damage response upon imposition of genotoxic stress 44 mediated via the inherent endonuclease activity of AAV2 Rep78 and Rep68 proteins. 45 We have previously proposed that in the breast cancer cells, AAV2 regulation of c-Myc activation could potentially mediate simultaneous growth stimulatory (G 1 /S, S, and G 2 phase targeting), and growth inhibitory (apoptosis associated DNA damage) signals which could represent a central unifying mechanism of AAV2-induced cell death in multiple breast cancer types.…”
Section: Aav2-mediated Manipulation Of Cell Cycle Check-points Is Relmentioning
confidence: 99%